Hallyu Versus Javanese Culture Among Youth in The City of Kediri: A Gender Perspective (Universitas Negeri Semarang, 2023)
One of the most massive cultural effects of globalization is the emergence of a global culture that has become a worldwide trend, such as Westernization. As a global culture, Westernization gained competitors, which was marked by the rise of Hallyu, which may be described as the Asian version of Westernization. This study aims to describe Hallyu versus Indonesian local (Javanese) culture among the people of the city of Kediri by using a mixed method. According to the study, Hallyu has begun to transform the status of Javanese culture as a global culture in the city of Kediri, as indicated by the increased interest of young people in the city of Kediri in symbols of Korean culture such as music, food, fashion, makeup, and even language. Hallyu can influence people and their attitudes. Women, for example, prefer to follow the flow of Hallyu more than men.